Repair of Pier Bridge Model Post-Earthquake - Justitiannisa, Innino; Gunadi, Riawan (International Journal of Integrated Engineering, 2023)
This study concentrates on the bridge pier model which was damaged by the earthquake and repaired using grouting and carbon wrapping materials. This research consists of a one pier bridge model with two steps of testing, namely step 1 in the form of a cyclic test of the pier bridge model which will be followed by step 2 in the form of structural repairs with grouting and carbon wrapping materials and retesting. to evaluate the performance of the structural repair technology used. This research will show the cyclic test results using the repair material applied to the same sbr latex concrete material test object. The test object used is a pier bridge model with dimensions of 0.25×0.25×1.68 meters. The material specifications used are concrete f'c 30, fy 400 MPa deformed longitudinal reinforcement and stirrups fy 240 MPa. The test was carried out with a constant axial load of 0.2.f'c.Ag and a cyclic lateral load. Structural performance analysis was carried out according to ACI 374.1-05. Step 1 cyclic test was carried out until the drift ratio was 3.5%. The lateral peak strength achieved was 8.606 tonf with indications of shear damage indicated by the number of cracks in the web area. The second step of the cyclic test was carried out to a drift ratio of 6.25% with a lateral peak strength of 8.640 tonf with indications of flexural damage. Cyclic test results show that repair with a grouting material and carbon wrap can restore peak strength, deformation capacity, and stiffness degradation.